Bringing the Empire Back In: The Gradual Discovery of the Ottoman Empire in Turkish Foreign Policy - Yanık, Lerna K. (Die Welt des Islams, 2016)
This article traces the emergence of references to the Ottoman Empire in the discourse and practice of Turkish foreign policy since the late 1940s. It argues that present-day emphasis on the Ottoman Empire and its legacy in Turkey has not happened in a vacuum, but rather has been a gradual process that has taken place over decades, helping to justify Turkey’s foreign policy. The article also shows that politicians from different sections of the political spectrum were crucial in reclaiming the Ottoman past in foreign policy. The consequences of this reclamation have been twofold. First, foreign policy, both in terms of practice and discourse, has become yet another venue, among many, for the continuous framing and reframing of Turkey’s past, paving the way for further Ottomanisation of the Turkish identity. Second, this Ottomanisation, or reclaiming of aspects that characterised the Ottoman Empire, has helped Turkey’s political actors justify and legitimise Turkey’s policies not only externally but, at times, also internally – as was the case in the 1990s, when some of these political actors tried to deal with Kurdish separatism by using the legacy of the Ottoman Empire.